PTH-105 How Ominous Is The "double-duct" Sign ?: A Single Centre Experience. (9th June 2014) - Gardner, T; Padala, K; Sinha, R; Greenaway, J; Joy, D
Abstract : Introduction: "Double-duct" sign on ERCP (Endoscopic retrograde cholangio-pancreatogram) is considered suggestive of pancreatic or biliary malignancy. This sign is frequently encountered in radiological imaging. We wish to investigate the prognostic value of the "double-duct" sign in patients who undergo Magnetic resonance cholangio-pancreatography (MRCP), attempting to define the associated features which would predict underlying malignant disease. 1, 2 Methods: A retrospective analysis of all the patients who underwent MRCP over a two year period; January 2011 to December 2012 was undertaken. All the radiological reports showing both a dilated common bile duct (CBD) and pancreatic duct (PD) or the "double-duct" sign were included. These were all interpreted and reported by specialist gastrointestinal radiologists. The demographics, liver biochemistry, final diagnosis and outcome for all patients with the "double-duct" sign were accessed using the radiology PACS® system, biochemical results WebICE®, hospital letters and case notes. Follow up information was available for a mean of 24months (range 12–36 months). Results: 1, 367 patients underwent MRCP examination over two year period. 46 patients (3.5% incidence) had "double-duct" sign (Table 1 ) with a mean age of 69.5 years. The ratio of male to female patients was (M:F) 12:11. The commonest cause of "double-duct" sign was choledocholithiasis (29.4%) followed by malignancy (26%). Patients with jaundice in the context of "double-duct" sign had a higher incidence of malignancy (48%). Nearly half of the patients, (21/46; 46%) with "double-duct" sign were anicteric. None of the anicteric patients were found to have malignancy. Of the anicteric patients, 29% (6/21) had completely normal liver test and the remaining 71% (15/21) had some abnormality of the liver enzymes (raised GGT and/or Alkaline phosphatase). Three patients in the anicteric group had benign tumours (2 cases of benign IPMN and 1 case of benign ampullary tumour). The benign nature was confirmed on clinical and radiological follow-up. No surgical intervention was deemed appropriate for any of these patients. All three remained anicteric over the period of follow-up (13 months; unrelated death, 18 and 36 months respectively). Our results show that "double duct" sign in the absence of jaundice makes a malignant aetiology unlikely. Conclusion: In patients with cross-sectional imaging evidence of "double-duct" sign, the absence of jaundice makes a malignant aetiology unlikely. Conversely, in jaundiced patients a malignant cause is much more likely. Figures from larger series are needed to support this conclusion. References: 1 Baillie J, et al. Biliary imaging: a review. Gastroenterology 2003; 125 (5):1565 2 Ahualli J. The double duct sign. Radiology 2007;244 (1):314–5 Disclosure of Interest: None Declared.